Kontroversi Visualisasi Hadis Berjilbab seperti Punuk Unta dalam Konten Media Sosial TikTok - Afifah, Bahiroh; Hasanah, Uswatun; Nurchalidin, Nurchalidin (Jurnal Penelitian Ilmu Ushuluddin, 2025)
This paper explains a problem, namely the visualization of the controversial Hadith about wearing a veil like a camel's hump in TikTok social media content. Given the current situation, the author argues that the visualized hadith understanding is still potentially not in accordance with the hadith scholars. This research directly observes several TikTok accounts and then conducts descriptive analysis and data analysis using Ferdinand de Saussure's semiotics to find out how the visualization of the hadith understanding of veiling like a camel's hump on TikTok social media content and is supported by primary data sources taken directly from the hadith content of veiling like a camel's hump on TikTok social media and hadith scholarly books in the form of Sahih Muslim bi Syarh An-Nawawi, digital applications such as Encyclopedi Hadith and Al-Maktabah Al-Syamilah, as well as relevant articles or literature. The results of this study indicate that the understanding of the Hadith of veiling like a camel's hump in the content posted on the social media accounts @nu_online and @alfateh_collection is in accordance with the explanation of the Hadith in the Sahih Muslim commentary book, where Imam An-Nawawi states, â€œtheir heads appear like the humps of camels that are tilted.â€ This refers to women who raise their heads like the humps of camels. This refers to women who raise their heads with veils, head coverings, and the like that are rolled up over the head, not at the back, so that they look similar to a camel's hump.